If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5z * z + -15 = 0 Multiply z * z 5z2 + -15 = 0 Reorder the terms: -15 + 5z2 = 0 Solving -15 + 5z2 = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 5z2 = 0 + 15 Combine like terms: -15 + 15 = 0 0 + 5z2 = 0 + 15 5z2 = 0 + 15 Combine like terms: 0 + 15 = 15 5z2 = 15 Divide each side by '5'. z2 = 3 Simplifying z2 = 3 Take the square root of each side: z = {-1.732050808, 1.732050808}
| 2x+2x+2= | | 4.2y=33.6 | | 23x+7-25x=6-9 | | 3w+3=228 | | 3*w*w+22w+40=0 | | 20h-36-4-4h=9h-99-1 | | 9y=x+3 | | s*s-10s+25=0 | | 15x+28(x-5)=75 | | 3.3x=2.8x+3.5 | | 23x+7-25x=-6-9 | | 8x+15-7x=-5-13 | | 3(m+1)=-15 | | m=a+d | | 40=-4(-5n-1)+6(6+7n) | | 2x-7=3forx | | 3(x+8)=9x+3-6x+21 | | -6m+-8=24 | | 6x-2-(x+2)=3x-18 | | 14=-7a-14 | | 2(6n-2)=8 | | -3+6(-3x-1)= | | 60x^2-122x+60=0 | | 16y=5(3y+62) | | Ax+bx+9=2 | | 1+9x=3(4x+1)-2 | | 13x^2+6x=20 | | 5x^2-29x=4x^2-7x-8 | | 5x+30x-6=35x+7 | | 0.66x+0.50=2.50 | | 6(x+8)+2(x-9)=-2x+40 | | (x+7)(x-1)=(2x+1) |